Prosthetic rehabilitation of a patient with cleidocranial dysplasia using dental implants-a clinical report - Sigmar Schnutenhaus; Werner Götz; Ralph G. Luthardt (SpringerOpen, 2021)
Abstract Adult patients with oral manifestations of untreated syndromic malformations usually exhibit a high degree of suffering. In this clinical report, we describe the implant-supported prosthetic treatment of a patient with cleidocranial dysplasia, a rare autosomal-dominant inherited malformation syndrome. Therapy for oral manifestations of cleidocranial dysplasia should be started in early childhood; however, the 26-year-old patient in the present study had not undergone orthodontic therapy in childhood. The treatment measures performed prior to this study were limited to the removal of several permanent teeth. Surgical pretreatment, placement of six implants each in the maxilla and mandible, and prosthetic restoration are described. The implantation was guided using a three-dimensional template. Long-term immediate temporary restoration and immediate loading of the implants were performed. The definitive prosthetic restoration was completed using fixed, acrylic resin-veneered screw-retained fixed dental prostheses. The clinical and radiological parameters observed in this case suggest that surgical and prosthetic procedure concepts from implantology can be adopted for patients with CCD.